e2rceramics - Radlinska, Emilka (Glasgow, Scotland : e2rceramics, 2006)
"e2rcermics is the blog of Emilka Radlinska. I'm a Polish Australian ceramic artist currently based in Glasgow, Scotland. I'm interested in the idea of real and virtual space, and how these spaces are understood in contemporary culture. What fascinates me in particular is the area where these two meet, and the resulting interaction between the real and the imaginary, the physical world with illusions."
Title from title screen (viewed on 30 Mar. 2010)
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://e2rceramics.com
Selected for archiving
Keywords: Blogs; Potters